2017
DOI: 10.1016/j.nicl.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional network disruptions in a kainic acid model of temporal lobe epilepsy

Abstract: We studied the graph topological properties of brain networks derived from resting-state functional magnetic resonance imaging in a kainic acid induced model of temporal lobe epilepsy (TLE) in rats. Functional connectivity was determined by temporal correlation of the resting-state Blood Oxygen Level Dependent (BOLD) signals between two brain regions during 1.5% and 2% isoflurane, and analyzed as networks in epileptic and control rats. Graph theoretical analysis revealed a significant increase in functional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 78 publications
7
43
1
Order By: Relevance
“…Consequently, repeated seizures could have led to increased functional connectivity between the amygdala and the prefrontal cortex, as shown in our study. Similar results were shown in a mouse model of temporal lobe epilepsy . Conversely, most studies in humans to date have demonstrated a decrease in functional fronto‐limbic connectivity and this finding has been linked to the increased incidence of mood disorders in patients with temporal lobe epilepsy .…”
Section: Discussionsupporting
confidence: 78%
“…Consequently, repeated seizures could have led to increased functional connectivity between the amygdala and the prefrontal cortex, as shown in our study. Similar results were shown in a mouse model of temporal lobe epilepsy . Conversely, most studies in humans to date have demonstrated a decrease in functional fronto‐limbic connectivity and this finding has been linked to the increased incidence of mood disorders in patients with temporal lobe epilepsy .…”
Section: Discussionsupporting
confidence: 78%
“…A major limitation of our study was the use of anesthetics, which may cause resting state network differences compared to awake animals. Isoflurane has been universally utilized in rodent neuroimaging studies . Some studies demonstrated that although instinct brain networks were still observed at deep levels of anesthesia, brain functional connectivity decreased with increased levels of anesthesia .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the TLE group of the present study, increased functional connectivity was observed in the visual cortex and mesencephalon to the hippocampal network ( Figure 4B), which is also in agreement with the results from other human neuroimaging studies. 32,33 Interestingly, Gill et al 34 recently revealed a significant increase in functional connectivity within the limbic network and the DMN in KA-treated rats compared to controls. The inconsistent results might have resulted from the choice of rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…between the various regions of the brain (Yousefnezhad and Zhang 2017). fMRI data have been used to understand the etiopathogenesis of neurological disorders such as Attention Deficit Hyperactivity Disorder (ADHD) (Mahanand, Savitha, and Suresh 2013), autism (Subbaraju et al 2017) and epilepsy (Gill, Mirsattari, and Leung 2017). Studies on the automatic diagnosis of neurological disorders from fMRI data have focused on analyzing the correlations between the regions to find discriminant activities.…”
Section: Introductionmentioning
confidence: 99%